EFEKTIVITAS MEDIA BINGO SEBAGAI MEDIA BELAJAR BAHASA MANDARIN TERHADAP PENINGKATAN PEMAHAMAN KOSAKATA SISWA KELAS 6 DI ELEMENTARY ANUGERAH SCHOOL SIDOARJO - Stevanny; Churota’ayun, Elisa (Universitas Widya Kartika Surabaya, 2024)
The Effectiveness of BINGO as a Learning Medium for Mandarin Vocabulary Comprehension among 6th-Grade Students at Elementary Anugerah School Sidoarjo. This study examines the effectiveness of BINGO as a learning medium for improving the Mandarin vocabulary comprehension of 6th-grade students at Elementary Anugerah School Sidoarjo. The BINGO game is utilized as a tool to enhance students' ability to read Hanzi, with the goal of fostering a greater interest in learning Mandarin through an engaging and enjoyable learning medium. This activity is supported by various methods, including the drill method, lecture method, and the use of PowerPoint, which together contribute to the success of the BINGO game. The BINGO game requires the use of PowerPoint as a platform for the BINGO board, which can be pre-designed to streamline the game's execution and save time. In conducting this activity, research methods are essential to assess the effectiveness of the approach. Therefore, the study employed pre-test and post-test methods to evaluate the students' condition before and after the implementation of the BINGO game, allowing for a thorough analysis of its impact on student learning outcomes.